Supply chain risk management enablers: A framework development through systematic review of the literature from 2000 to 2015 - Irène Kilubi; Hans-Dietrich Haasis (International Journal of Business Science & Applied Management (IJBSAM), 2015)
The present paper delivers a robust and systematic literature review (SLR) on supply chain risk management (SCRM) with the purpose to a) review and analyse the literature concerning definitions and research methodologies applied, to b) develop a classificatory framework which clusters existing enablers on SCRM, and to c) examine the linkage between SCRM and performance. The findings reveal that not only is SCRM loosely defined, but that there are various fragmented supply chain risks enablers and that there is a strong need for a clear terminology for its building enablers. In addition to that, the review points to a lack of empirical confirmation concerning the connection between SCRM and performance. This paper contributes an overview of 80 peer-reviewed journal articles on SCRM from 2000 to the beginning of 2015. We offer an overarching definition of SCRM, synthesise and assemble the numerous enablers into preventive and responsive strategies by means of a conceptual framework. Moreover, indicating the social network theory (SNT) as a potential theoretical foundation for SCRM, we further contribute to the supply chain management (SCM) literature by providing propositions that guide future research.
Keywords: 650; supply chain risk management; supply chain risk(s); supply chain performance; supply chain disruption(s); systematic literature review; enabler(s); conceptual framework